2022
DOI: 10.1097/j.jcrs.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of femtosecond laser–assisted cataract and refractive lens surgery in patients with prior radial keratotomy

Abstract: FLACS- or FL-assisted RLE surgery in RK patients has a high risk for anterior capsule tears and should be avoided. Thickened incisional scars are potential sources of incomplete laser penetrance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Furthermore, the application of LASERs in cataract surgery began to be investigated in the seventies [6,7,[25][26][27][28]. The argon laser, whose wavelength lies in the visible light spectrum, was the first laser to be used clinically in Ophthalmology [7].…”
Section: Cataract Surgery -Femtosecond Lasermentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the application of LASERs in cataract surgery began to be investigated in the seventies [6,7,[25][26][27][28]. The argon laser, whose wavelength lies in the visible light spectrum, was the first laser to be used clinically in Ophthalmology [7].…”
Section: Cataract Surgery -Femtosecond Lasermentioning
confidence: 99%
“…These corneal incisions are selfsealing and provide a gateway to access the anterior chamber. The precision of the incision and the consistency of its Femtosecond laser architecture enable better postoperative healing, allowing for better control of postoperative infection [6,7].…”
Section: Cataract Surgery -Femtosecond Lasermentioning
confidence: 99%
See 1 more Smart Citation
“…
Comment on: New thin-film adhesive for sealing full-thickness corneal incisions in rabbits We read with great interest the article by Tan et al 1 This study concluded that the use of a laser-activated thin-film adhesive was efficacious in sealing 2.0 mm penetrating corneal incisions, with greater burst pressures compared with sutures or self-seal. We congratulate the authors for their fine work.Werner et al reported 8 cases of toxic anterior segment syndrome after uneventful phacoemulsification, which were caused by antibiotic/steroid ointment that gained access to the eye.
…”
mentioning
confidence: 99%
“…Comment on: Outcomes of femtosecond laser-assisted cataract and refractive lens surgery in patients with prior radial keratotomy We would like to congratulate Trinh et al for their excellent publication, which deals with individuals who in their younger days underwent radial keratotomy (RK) and who now had femtosecond laser-assisted cataract surgery (FLACS). 1,2 We have performed FLACS ever since we reported on our first 6 eyes a couple of years ago. 3 Our experience, however, differs from the one described in the recent paper.…”
mentioning
confidence: 99%